1992
DOI: 10.1590/s0074-02761992000700011
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome 9 deletion in Plasmodium falciparum results in loss of cytoadherence

Abstract: Many lines of Plasmodium falciparum undergo a deletion of the right end of chromosome 9 during in vitro culture accompanied by loss of cytoadherence and gametocytogenesis. Selection of cytoadherent cells from a mixed population co-selects for those with an undeleted chromosome 9 and the selected cells produce gametocytes. The deletion also results in loss of expression of PfEMP1, the putative cytoadherence ligand, suggesting that PfEMP1 or a regulatory gene controlling PfEMP1 expression and gametocytogenesis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Closer examination of the segregating CNVs that were detected only at the lower significance threshold (LOD < 5) revealed several reasons for weaker signal: CNVs with highly skewed inheritance in the progeny population (e.g. Chr 9 [68] - Additional file 10B and Chr 11 [44]); loci with overlapping or neighboring CNVs in the parents (Additional file 10A-i); and complex multiallelic CNVs, i.e. region overlapping a mixture of amplified as well as deleted regions in the parent genomes or de novo CNV region overlapping a segregating CNV region in at least a single progeny (Additional file 11B and 11C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer examination of the segregating CNVs that were detected only at the lower significance threshold (LOD < 5) revealed several reasons for weaker signal: CNVs with highly skewed inheritance in the progeny population (e.g. Chr 9 [68] - Additional file 10B and Chr 11 [44]); loci with overlapping or neighboring CNVs in the parents (Additional file 10A-i); and complex multiallelic CNVs, i.e. region overlapping a mixture of amplified as well as deleted regions in the parent genomes or de novo CNV region overlapping a segregating CNV region in at least a single progeny (Additional file 11B and 11C).…”
Section: Resultsmentioning
confidence: 99%
“…Emergence of CNV under in vitro conditions have been reported widely in P. falciparum with laboratory adaptation [68,91,92], under long term laboratory culture [19-22] and under drug pressure [21,23,67,90,93]. It has been widely postulated that parasites have fewer constraints during in vitro culture conditions such that growth advantages can be gained from decreased investment in activities such as protein exportation, knob construction, display of cytoadhesive molecules and variant antigens, and production of gametocytes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression studies not only provide evidence that increases in Pfgdv1 activity modulate gametocyte production in a dynamic fashion, but may also provide a molecular tool to augment the production of gametocytes to facilitate the development of transmission-blocking reagents [46]. Previous work demonstrated that episomal expression of a neighboring gene Pfgig (PFI1720w) increased Pfs16 expression in a non-gametocyte producing line, but did not restore gametocyte production [29]. Pfgig was intact in the G def line used in this study and expression was not significantly affected by the loss of Pfgdv1 ; however, it is possible that it could act in conjunction with Pfgdv1 to stimulate gametocytogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission stages are no longer selected for, which could explain the variation in isolates but not for individual clones. The probable mechanism accounting for this variation is chromosome deletion, especially chromosome 9 subtelomeric deletion, which is commonly observed in cultured parasites [65,74]. One could also imagine single gene defects, for instance, the knock-out of the Pfg27 leads to loss of sexual phenotype [75].…”
Section: Commitment To Gametocytogenesismentioning
confidence: 99%